Anda di halaman 1dari 6

FULLY WORKED SOLUTIONS

CHAPTER

7 LIMITS AND CONTINUITY

Focus on STPM 7

1 (a) |x + 3| =

{ x 3, x < 3

x + 3, x 3
2 (a) lim h(x) = 2


x 1
1 + p = 2
p = 3
x = 1 is in the range
3 x < 0, so the
part of the function
(x + 1)(x 3) x + p is used.
For x < 3, f(x) =
x+3 (b) Since lim h(x) exists,
x3
= x 1 limh(x) = lim+h(x)
(x + 1)(x + 3) x3 x3
x2 k
For x 3, f(x) =
x+3
(3) k = 3 + 3
2
=x+1
k = 9
Hence, in the non-modulus form, x+3

{
x 1, x < 3 Since lim h(x) exists,
x0
f(x) = lim h(x) = lim+ h(x)
x + 1, x 3 x0 x0
x+3
(b) The graph of f(x) is as shown below. 0+3=e 0q

e xq
y = x 1 y ln 3 = q
q = ln 3
2
y=x+1 q = ln 31
q = ln1
1 3

{
x
3 2 1 0 (c) x 2 9, x < 3
1
h(x) = x + 3, 3 x < 0
3e ,
x
x0
2
ex
e xq =
(c) lim f(x) = (3) 1 eq
x3
ex
=2 = 1
ln
e 3
lim+f(x) = (3) + 1 ex
x3 =
= 2 1
3
(d) lim f(x) does not exist because lim = 3e x
x3 x3

f(x) lim+f(x).
x3

ACEAHEAD
ACE AHEAD Mathematics
Mathematics (T)
(T) Second Term
First Term ThirdEdition
Second Edition
Oxford Fajar Sdn. Bhd. 2016
Oxford Fajar Sdn. Bhd. 2015 1

Chapter 07.indd 1 11/22/2016 12:16:16 PM


y

(1, 8.15)
Since limfog(x) = limfog(x) = 6
x3 x3+

then limfog(x) = 6
x3

y = 3e x
4 In the non-modulus form,

{
x 2 1, x < 1
3
f(x) = x2 + 1, 1 x < 1
3

2
+

(x 2)(x 3), x 1
x

y = x2 9
=
y

1
x
4 3 2 1 0 1 2 (a) y

3 (a) fog = f [g(x)] 2


1 1 y = (x 2)(x 3)
= f y = x2 1
x3 1 0 1 2 3 4
x


1
=2 3+

1 y = x 2 + 1

x3
= 2(3 + x 3)
(b) (i) lim f(x) = 12 1
= 2x x1

The domain of fog is the same as the =0


domain of g, i.e. {x : x , x 3}, lim f(x) = 12 + 1
x1+
because the domain cannot take the
value 3, the range of fog cannot take =0
the value 2x = 2(3) f(1) = 12 + 1
= 6.
=0
Hence, the range of fog is {y : y ,
y 6}. Since lim f(x) = lim f(x)

x1 x1+

(b) y = f(1)
=0
6
then f (x) is continuous at x = 1.
(ii) lim f(x) = 12 + 1
x1

x =0
0 3
lim f(x) = (1 2)(1 3)
x1+
=2
y = 2x
Since limf(x) limf(x), then

x1 x1+

limf(x) does not exist.


x1
limfog(x) = 2(3) and limfog(x) = 2(3)
(c)  
Hence, f
(x) is not continuous at
x3 x3+

= 6 = 6 x = 1.

ACE AHEAD
ACE AHEAD Mathematics
Mathematics(T)
(T)Second Term
First Term Third Edition
Second Edition
2 Oxford Fajar Sdn. Bhd. 2016
Oxford Fajar Sdn. Bhd. 2015

Chapter 07.indd 2 11/22/2016 12:16:22 PM


5 (a) In the non-modulus form, (d) y

{
x2 , x < 0
x 4

f(x) =
x2 , x 0
x 2
y = 2x

{
x, x < 0
y = x
f(x) =
x, x0 x
2 0 2

In the non-modulus form, 3x + 1


6 f(x) =

{
x + 3x , x < 0 x+2

2 As f(x), the denominator of f(x) 0
g(x) = x+20
x + 3x , x 0
 x 2
2
Hence, x = 2 is the vertical asymptote.

{
x, x < 0
3x + 1
g(x) = lim f(x) = lim
x
x x + 2
2x, x 0


3x 1
+
x x

{
(b) g(x), x < 0 = lim
x x 2
g of(x) = +
x x


g(x), x0 1
3+
x

{
x, x < 0 = lim
x 2
of(x) =
g 1+
x

2x, x 0 3+0
=
1+0
(c) limgof(x) = 0
=3
x0
=0 Hence, y = 3 is the horizontal asymptote.
limgof(x) = 2(0)
+
y
x0
=0
gof(0) = 2(0)
=0 3

Since limgof(x) = limgof(x)


x0 x0+

= f(0)
=0 1
2
then gof(x) is continuous at x = 0. x
2 0
1
3

ACEAHEAD
ACE AHEAD Mathematics
Mathematics (T)
(T) Second Term
First Term ThirdEdition
Second Edition
Oxford Fajar Sdn. Bhd. 2016
Oxford Fajar Sdn. Bhd. 2015 3

Chapter 07.indd 3 11/22/2016 12:16:26 PM


7 y (b) f is not continuous at x = 0 because
lim f(x) f(0).
y= x+1 x0

y = x 1 1 0
y=x1

(c) y
1
5
x
1 0 1 4

3 y = ex
2.7
1 2

1
Substituting x
1 0 1 2
(a) lim f(x) = (1) 1

x = 1 into
x1
= 0 x 1.
y=x+1

Substituting
lim f(x) = 1 + 1 x = 1 into 9 (a) lim- g( x ) = lim+ g( x )
x1+ x -1 x -1
x + 1.
a - ( -1) = 2( -1) + 3
2
=0
Substituting a -1 = 1
lim f(x) = 1 + 1 x = 1 into a=2
x1
x + 1. lim g( x ) = lim+ g( x )
= 2 x 1- x 1

Substituting b
2(1) + 3 =
lim f(x) = 1 1
+
x = 1 into 1
x1
=0 x 1. b=5
(b) y
(b) f (x) is continuous at x = 1 because
5
lim f(x) = lim f(x) = f(1) = 0
x1 x1+
4
but f (x) is not continuous at x = 1 y = 2x + 3 3 5
because lim f(x) lim f(x). 2
y=
x
x1 x1+

8 (a) (i) lim f(x) 1



x0 x
= 0 + 1 3 2 1 0 1 2 3 4 5 6

= 1 2
y = 2 x2

(ii) lim f(x)


x0+

= e0
= 1
7
(iii) Since lim f(x) = lim f(x) = 1,
x0 x0+

then lim f(x) = 1.


x0

ACE AHEAD
ACE AHEAD Mathematics
Mathematics(T)
(T)Second Term
First Term Third Edition
Second Edition
4 Oxford Fajar Sdn. Bhd. 2016
Oxford Fajar Sdn. Bhd. 2015

Chapter 07.indd 4 11/22/2016 12:16:32 PM


10 (a) lim- f ( x ) = 4 - 3 - 1 = 2 y
(c)
x 3

lim f ( x ) = 32 - 4(3) + 5 = 2
x 3+

lim f ( x ) = 2
x3
1
f is not continuous at x = 3 because
lim f(x) f(3).
x3 x
0

2 1
1
y
(b)
10

8
x2 + 2x + 4
7

6
)
12 (a) x - 2 x 3 + 0 x 2 + 0 x - 8

5 x3 - 2 x 2
4 2x2 + 0x
3
2x2 - 4x
2

1 4x - 8
x 4x - 8
3 2 1 0 1 2 3 4 5 6
0
6( x - 2)
lim

{
x 2 x3 - 8
1 ex, x < 0
6( x - 2)
11 (a) f(x) = 1, x=0 = lim
x 2 ( x - 2)( x 2 + 2 x + 4)

e 1, x > 0
x
6
= 2
lim f(x ) = 1 - e 0 = 1 - 1 = 0 2 + 2( 2) + 4
x 0-
6 1
lim f(x ) = e 0 - 1 = 1 - 1 = 0 = =
x 0+ 12 2
Since lim- f(x ) = lim+ f(x ), then lim f(x ) exists. x -8
x0 x0 x0 (b) lim
x 8
6 - x-2
lim- f(x ) = lim+ f(x ), then lim f(x ) exists.
x0 x0 x0

= lim
( x - 8) ( 6 + x-2 )
(b) f is not continuous at x = 0 because x 8
( 6 - x-2 )( 6 + x-2 )
lim f(x ) = 0 f(0)


x 0

f is continuous for {x : x < 0 or x > 0}. = lim


( x - 8)) ( 6 + x-2 )
x 8 6 - ( x - 2)

= lim
( x - 8) ( 6 + x-2 )
x 8 8-x
= lim -
x 8
( 6 + x-2
)
( )
ACEAHEAD
ACE AHEAD Mathematics (T) Second Term ThirdEdition
Edition
= - 6 Mathematics
+ 8 - 2(T) First Term Second
Oxford Fajar Sdn. Bhd. 2016
Oxford Fajar Sdn. Bhd. 2015 5

= -2 6
Chapter 07.indd 5 11/22/2016 12:16:35 PM
x 8
6 - x-2

= lim
( x - 8) ( 6 + x-2 )
x 8
( 6 - x-2 )( 6 + x-2 )
= lim
( x - 8)) ( 6 + x-2 )
x 8 6 - ( x - 2)

= lim
( x - 8) ( 6 + x-2 ) x + 1,

x <1
x 8 8-x f ( x ) = m 2 - 2, x =1
1 + n, x >1
= lim -
x 8
( 6 + x-2
)

=- ( 6 + 8-2 ) (a) If lim f ( x ) exists,


x 1

= -2 6 lim f ( x ) = lim+ f ( x )
x 1- x 1

1+1 =1+ n
x2 -1
, x < 1, n =1
x - 1
13 f ( x ) = m 2 - 2, x = 1, (b) If f is continuous at x = 1,
1- x lim = f (1)
+ n, x > 1. x 1
x - 1
2 = m2 - 2
( x + 1)( x - 1) m2 = 4
, x < 1,
x -1
m = 2
f ( x ) = m 2 - 2, x = 1,
x -1
+ n, x > 1.
x -1

ACE AHEAD Mathematics (T) Second Term Third Edition


6 Oxford Fajar Sdn. Bhd. 2016

Chapter 07.indd 6 11/22/2016 12:16:37 PM